KOORDINASI ANTARA PEMERINTAH PROVINSI RIAU DAN PEMERINTAH KABUPATEN ROKAN HILIR DALAM MENANGANI KEBAKARAN HUTAN DAN LAHAN (KARHUTLA) DI ROKAN HILIR TAHUN 2010-2013 - Shahira Harun; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The study, entitled "Coordination between the Government of Riau Province and the Government of Rokan Hilir in handling forest fires (Karhutla) in Rokan Hilir on 2010-2013". Land and forest fires in Rokan Hilir is a serious problem, so treatment requires integration of resources or involving stakeholders in the regions. Various attempts to control land and forest fires has been done by the Government of Riau Province and the Government of Rokan Hilir, but the course of the second vertical coordination of the local government level is not optimal. Therefore, the authors formulate the problem regarding the implementation of the coordination and the cause of the lack of coordination between the provincial government and the Government of Rokan Hilir in dealing with land and forest fires in Rokan Hilir on 2010-2013.This study shows how coordination has implemented the Riau Provincial Government and the Government of Rokan Hilir tackle land and forest fires in the form: held a coordination meeting between officials; held a formal meeting between officials; create a circular chain necessary to officials; lifting coordinator; making organizations handbooks, guidelines for work procedures, and sets of rules; and is associated with a nexus. In addition the results of this study also describes some of the reasons behind the lack of coordination, namely: lack of supervision, lack of communication, lack of awareness of the importance of coordination, lack of participants who have the competence, financial support and limited facilities, lack of political commitment, and other inhibiting factors.The conclusions of this study mentions how the implementation of coordination between the Government of Riau Province and the Government of Rokan Hilir in dealing with land and forest fires in Rokan Hilir on 2010-2013 has been quite good, but the intensity of the implementation of such coordination is still lacking done by the Riau provincial government to local government Rokan Hilir and vice versa. Cause of the weak implementation of such coordination is the lack of supervision, lack of communication, lack of awareness of the importance of coordination, lack of participants who have the competence, financial support and limited facilities, lack of political commitment, and other inhibiting factors. The authors hope the results of this study may help provide information in dealing with land and forest fires.Keywords: Coordination, Local Government, Government of Riau Province, the Government of Rokan Hilir, Forest Fires